An outbreak of oropharyngeal tularaemia linked to natural spring water - (:unkn) unknown (MICROBIOLOGY SOC, 2009)
A tularaemia outbreak was investigated involving 188 suspected cases in the Kocaeli region of Turkey between December 2004 and April 2005. A case-control study comprising 135 laboratory-confirmed cases and 55 controls was undertaken to identify risk factors for the development of the outbreak and to evaluate laboratory diagnostic methods. Tularaemia was confirmed by a microagglutination test (MAT) titre of >= 1 :160 in 90 of the patients. In MAT-negative sera, 23/44 (52 %) were positive by ELISA with Francisella tularensis LPS and 1/9 (111 %) by Western blotting with this antigen. A species-specific PCR was positive in 16/25 (64 %) throat swabs and 8/13 (62 %) lymph node aspirates. Multivariate analysis showed that drinking natural spring water was the leading risk factor for the development of tularaemia (P=0.0001, odds ratio 0.165, 95 % CI 0.790-0.346). The outbreak ceased after abandonment of the suspected natural water springs.
Keywords: TURKEY